Microglial Corpse Clearance: Lessons From Macrophages - Márquez-Ropero, Mar; Benito, Eva; Plaza-Zabala, Ainhoa; Sierra, Amanda (Frontiers in Immunology, 2020)
From development to aging and disease, the brain parenchyma is under the constant threat of debris accumulation, in the form of dead cells and protein aggregates. To prevent garbage buildup, the brain is equipped with efficient phagocytes: the microglia. Microglia are similar, but not identical to other tissue macrophages, and in this review, we will first summarize the differences in the origin, lineage and population maintenance of microglia and macrophages. Then, we will discuss several principles that govern macrophage phagocytosis of apoptotic cells (efferocytosis), including the existence of redundant recognition mechanisms (“find-me” and “eat-me”) that lead to a tight coupling between apoptosis and phagocytosis. We will then describe that resulting from engulfment and degradation of apoptotic cargo, phagocytes undergo an epigenetic, transcriptional and metabolic rewiring that leads to trained immunity, and discuss its relevance for microglia and brain function. In summary, we will show that neuroimmunologists can learn many lessons from the well-developed field of macrophage phagocytosis biology.